Metal-Organic Framework-Derived Honeycomb-Like Open Porous Nanostructures as Precious-Metal-Free Catalysts for Highly Efficient Oxygen Electroreduction - Zhu, Qi-Long; Xia, Wei; Akita, Tomoki; Zou, Ruqiang; Xu, Qiang (Advanced materials (Weinheim), 2016)
Honeycomb‐like porous carbon nanostructures are rationally constructed from a metal–organic framework composite. The unique architecture with uniformly distributed high‐density active sites significantly enhances the electrocatalytic performance by increasing the accessible active sites and enhancing mass transport of the gas and electrolyte, rendering the resulting catalyst adequate in reaching the desired catalytic performance afforded by Pt for the oxygen reduction reaction.